Conceptual framework for a comprehensive competence in managing challenging behaviour: The views of trained instructors. Issue 4 (9th January 2021) - Tölli, Sirpa; Kontio, Raija; Partanen, Pirjo; Häggman‐Laitila, Arja
Accessible summary: What is known on the subject?: There is body of knowledge available about the harms associated with restrictive interventions used in behaviour management, service users' perceptions of the use of restraints, and staff competence in behaviour management. The staff perspective has been studied in terms of staff exposure, responses to and prevention of aggression, staff‐related factors associated with service user aggression, and staff attitudes and perceptions towards violence. The definitions of competence in behaviour management provided in training interventions are fragmented and based on unilateral measurements. Training interventions with the purpose of enhancing staff competence in behaviour management are organized regularly, yet there is a lack of clarity on how effective these interventions are. Inadequate conceptual understanding of behaviour management can weaken the effectiveness of these interventions. What this paper adds to existing knowledge?: Our study produced new knowledge by providing a preliminary conceptual framework that can be used to comprehensively describe and assess competence in managing challenging behaviour and to cover safely the whole care process. Humane care and ethical sensitivity should be the premises of interaction with people in distress. We also pointed out the needs for conceptual clarification of the concepts of confidence, support and restraint. We provide important new insight into the leadership and cultural issues of behaviour management that is relevant for patients, staff members and healthcare organizations. We found that staff members do not consider service user safety and workplace safety as opposing issues. Further, we provide new perspectives for prevention, the risk assessment process and effective communication in the context of behaviour management. What are the implications for practice?: A comprehensive understanding of the competences related to behaviour management will foster universal definitions for "support" and "restraint, " which can then be used to ensure that the best practices are used for behaviour management. Organizational culture and participative leadership on behaviour management should be developed with a special focus on safety issues, common understanding of comprehensive competence, risk assessment and prevention, views regarding the use of restraints, and teamwork. Abstract: Introduction: Previous research concerning staff views of behaviour management has not considered instructors' views. The definitions of competence in behaviour management are fragmented, which can undermine the effectiveness of training interventions. Aim/Question: This study aimed to describe Finnish and British Management of Actual or Potential Aggression instructors' perceptions of safety and behaviour management‐related competences and create a conceptual framework for comprehensive competence. Method: An explorative‐descriptive qualitative approach with purposive sampling ( N = 22), semi‐structured interviews and abductive content analysis. Results: Conceptual framework of comprehensive competence in managing challenging behaviour includes five categories—knowledge, skills, attitude, confidence and ethical sensitivity—and 21 subcategories. Competent staff and supportive leadership ensured safety, while inconsistent risk management culture, the health and behaviour of service users, and inadequate staff orientation endangered safety. Discussion: The study produced new knowledge of safety issues and competences from the perspective of the instructors who deliver behaviour management training. Implications for practice: Competence to manage challenging behaviour should be developed based on our conceptual framework to provide an effective and safe training. Prevention, the risk assessment process, alternative communication, and the definitions of "confidence, " "support" and "restraint" should all be sufficiently addressed in future training.